2016
DOI: 10.2147/phmt.s99191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum zinc, selenium, and prolactin concentrations in critically ill children

Abstract: BackgroundIn critically ill patients, there are reduced stores of antioxidants, which are associated with increased organ failure and even higher mortality. Trace elements, especially zinc and selenium, are the cornerstone of the antioxidant defense in acute systemic inflammatory response syndrome. Prolactin (PRL) is the counterregulatory stress hormone that prevents cortisol/stress-induced lymphocyte apoptosis. The aim of our study is to detect the serum levels of zinc, selenium, and PRL hormone as important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
4
0
1
Order By: Relevance
“…It is involved in the immune response and can inhibit the growth of bacterial species [ 19 ]. The decrease in PIP found in our study could be related to a decrease in prolactin, which has been described in pigs with inflammation [ 20 ] and humans with sepsis [ 21 ].…”
Section: Discussionsupporting
confidence: 74%
“…It is involved in the immune response and can inhibit the growth of bacterial species [ 19 ]. The decrease in PIP found in our study could be related to a decrease in prolactin, which has been described in pigs with inflammation [ 20 ] and humans with sepsis [ 21 ].…”
Section: Discussionsupporting
confidence: 74%
“…Nangliya et al also reported that serum zinc concentrations were correlated with the severity of liver cirrhosis [44]. In addition, Elmasry et al reported that the serum zinc concentrations were inversely correlated with the organ failure index and organ dysfunction score in critically ill children in the pediatric intensive-care unit [45,46]. Although the mechanism of disease-related zinc concentration was unclear in these previous reports, our results suggest that amount of infiltrating monocytes with these inflammatory conditions was related with disease severity and inversely associated with the zinc serum concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive Cu in the human organism has been recognized in cell damage in sepsis and HF because it is involved in production of ROS and results in deterioration of the in ammation and cardiac systolic dysfunction. Previous studies had shown that hypozincemia was associated with lymphopenia, thymic atrophy and dysfunction of cell-and antibody-mediated immunity (49,50), which could decrease lots of pre-B and pre-T cells lead to the immune paralysis in both sepsis and cardiac dysfunction (51,52). Studies revealed that elevated TNT was related to higher short-term or long-term morality in patients with sepsis or septic shock (53,54).…”
Section: Discussionmentioning
confidence: 99%